1998
DOI: 10.2307/3180280
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rental Rates on the Extension of Conservation Reserve Program Contracts

Abstract: This paper presents a model for estimating the change in conservation reserve program (CRP) contract extensions as a function of the change in rental rates. The majority of the CRP contracts on approximately 36 million acres of enrolled land are expiring within the next two years, with the result that re-enrollment decisions by farmers and the federal government will have high budgetary implications. In a modification of the traditional dichotomous choice method for estimating random utility models in consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 9 publications
0
41
3
Order By: Relevance
“…If the current GTGP can be renewed with the same payment (250 yuan/mu), Ͼ90% of GTGP land plots could be saved from reconversion. This finding is quite different from that in studies of the Conservation Reserve Program (CRP) in the United States, where maintaining enrolled land was much more expensive than the original cost (42). Compared to the land set aside in the CRP, the GTGP land plots have high costs of reconversion due to reforestation in the land plots.…”
Section: Effects Of Social Norms and Conservation Payment On Re-enrolcontrasting
confidence: 54%
See 2 more Smart Citations
“…If the current GTGP can be renewed with the same payment (250 yuan/mu), Ͼ90% of GTGP land plots could be saved from reconversion. This finding is quite different from that in studies of the Conservation Reserve Program (CRP) in the United States, where maintaining enrolled land was much more expensive than the original cost (42). Compared to the land set aside in the CRP, the GTGP land plots have high costs of reconversion due to reforestation in the land plots.…”
Section: Effects Of Social Norms and Conservation Payment On Re-enrolcontrasting
confidence: 54%
“…One extra mu of cropland increased the probability of re-enrollment by 13.8% (Table 1). In contrast to other studies (42), livestock breeding did not affect people's re-enrollment intentions. Moreover, no effects of household size and total area of GTGP land plots on program re-enrollment were found ( Table 1).…”
Section: Effects Of Household Economic and Demographic Conditionscontrasting
confidence: 50%
See 1 more Smart Citation
“…In the context of the CRP, there have long been efforts to understand what happens to land when it exits the program, but no causal attribution of these results to CRP experience. Early surveys (for example, Cooper and Osborn, 1998;Johnson et al, 1997) Roberts and Lubowski (2007) look carefully at selectivity in CRP exit to estimate that 58% of CRP land would enter farming if the program were eliminated, and conclude that a large segment of ex-CRP land persists in conservation. However, none of these results can be compared to a counterfactual in which the land had never entered the CRP, since CRP land is likely to be quite different from non-CRP land.…”
mentioning
confidence: 99%
“…As suggested by the theories of reasoned action and planned behavior (Ajzen 1985, Fishbein andAjzen 2011), willingness or intention is often the strongest predictor of actual behavior. For example, the observed amount of cropland that households reenrolled in the Conservation Reserve Program in 2001 in the United States was close to that predicted based on survey data on households' stated willingness to participate, which was collected in 1993 (Cooper and Osborn 1998). In other contexts, such as purchase decisions, some literature indicated that stated and actual choices are highly correlated (e.g., Loureiro et al 2003).…”
Section: Modeling Household Willingness To Participate In Future Graimentioning
confidence: 99%